2010
DOI: 10.2528/pier09111004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effects of GSM Bands to the Electromagnetic Pollution in the Rf Spectrum

Abstract: Abstract-In this study, electromagnetic (EM) pollution measurements in crowded residential areas were performed, and statistical analysis of values recorded for the EM sources causing pollution was carried out. The actual measurement values and estimated values by the analysis model obtained through the statistical analysis were compared. Also, amplitude fluctuations of the electromagnetic radiations from EM pollution sources were detected for a long time, and statistical analyses were made. EM field levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 9 publications
0
25
0
3
Order By: Relevance
“…The number of cell towers is increasing rapidly, and electromagnetic (EM) waves emitted from the Base Station Antennas (BSAs) may have adverse effects on human beings or on other living animals [1][2][3][4][5]. It has also been reported that continuous exposure to microwave radiation from cell phone towers causes serious health problems over the years [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The number of cell towers is increasing rapidly, and electromagnetic (EM) waves emitted from the Base Station Antennas (BSAs) may have adverse effects on human beings or on other living animals [1][2][3][4][5]. It has also been reported that continuous exposure to microwave radiation from cell phone towers causes serious health problems over the years [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Mastery of phenomena related to the propagation of a laser beam in an optical and thermal turbulence is also essential when trying to respond to the concerns encountered in a large number of technological applications based on the laser, such as medical diagnostic with laser [5], laser radar [6], laser probing of atmospheric properties [7], laser satellite communication and Earth-to-space communications [8], submarine detection [9], monitoring and remote sensing [10], laser weapons and laser defence missiles [11]. .…”
Section: Introductionmentioning
confidence: 99%
“…Measuring and evaluating the RF-EMF emitted by base stations and wireless systems, and controlling their compliance with standards/limit values is of great importance for human health and helps to take precautions. Therefore, many researches [1][2][3][4][5][6][7][8][9] have been focused on the measurement and assessment of electric field strength (E) that is emitted from wireless devices. Determining especially the change in emitted E levels from base stations depending on usage density at particular times of day has great importance.…”
Section: Introductionmentioning
confidence: 99%